Kualitas Karkas Domba Lokal yang Diberi Pakan Jerami Padi Fermentasi dengan Suplementasi Minyak Kedelai - Peni Patriani; Juni Sumarmono; Wardhana Suryapratama (Jurnal Agripet, 2010)
Carcass quality of local sheep fed fermented rice straws supplemented with soybean oilABSTRACT. The aim of this study was to determine if supplementation of soybean oil in the ration in order to increase conjugated linoleic acid of meat has concurrent effects on carcass characteristics and qualities of thin-tailed sheep. Sheep were fed fermented ricestraws supplemented with 0, 3 and 6% soybean oil. The experimental design used was a Randomized Completely Block Design. Eighteen sheep with initial age of 6-8 months and initial bodyweight of 17.46 1.61 kg were used. The treatments consisted of soybean oil supplementation 0, 3 and 6%. Variables measured were carcass conformation, GR thickness, backfat thickness, subcutaneous fat score, and kidney and pelvic fat score. Result showed that sheep fed ration with 0 % soybean oil produced carcass with carcass conformation score of 8.50 1.05, GR thickness 11.50 1.05 mm, back fat thickness 2.67 0.82 mm, subcutaneus fat score 3.50 0.55 mm, kidney and pelvic fat score 2.00 0.00. Sheep feed ration with 3% soybean oil; carcass conformation score 8.67 1.21, GR thickness 11.67 1.21 mm, back fat thickness 2.83 0.98 mm, subcutaneus fat score 3.50 0.55, kidney and pelvic fat score 1.83 0.4. Sheep feed ration with 6% soybean oil; carcass conformation score 9.00 1.26, GR thickness 12.50 1.52 mm, back fat thickness 3.33 0.82 mm, subcutaneus fat score 3.50 0.55, kidney and pelvic fat score 1.83 0.41. Score of carcass conformation, thickness of GR, thickness of back fat, score of subcutaneus fat, and score of kidney-pelvic fat were not influenced by supplementation of soybean oil. In conclusion, suplementation soybean oil in the ration to increase conjugetaed linoleic acid has no significant concurrent effect on carcass quality characteristics of local sheep.